ARISAN ONLINE SISTEM MENURUN DALAM FIQIH MUAMALAH KONTEMPORER DI GRUP WHATSAPP: (Studi Kasus Pada Grup Arisan By.NAB di Grup Whatsapp di Dusun Jatisari Desa Krenceng Kecamatan Kepung) - Dwi Andayani; Alfina Khoirun Nisak (Jurnal Ilmiah Ekonomi Syariah, 2025)
Abstarct This research uses a qualitative field approach, meaning the researcher comes directly to the research location to collect data through interviews to find out the conditions directly, thus producing qualitative descriptive data. The objectives of this study are: 1) To determine the mechanism of online arisan with a descending system in the Arisanby.NAB WhatsApp group; 2) To determine the descending system of online arisan in WhatsApp groups according to contemporary muamalah fiqh. After conducting research on the practice of online arisan in the By.NAB WhatsApp group, it has fulfilled the requirements of qardh and the pillars of qardh, namely the presence of muqridh (lender), the presence of muqtaridh (people who owe), the presence of muqtaradh (goods lent) and sighat akad (agreement between two parties who owe). It can be seen that the owner, admin and all members have fulfilled the requirements, namely being baligh or mature and sane. However, in practice, there are things that deviate from the provisions, namely in the aspect of sighat requirements because in practice there are elements of usury and gharar. Keywords : Online Arisan, Contemporary Muamalah, Whatsapp